Micropyramid-patterned, oxygen-permeable bottomed dish for high density culture of pancreatic islets. (1st January 2023) - Myrick, Ryan J; Shang, Kuang-Ming; Betts, Jonathan F; Gonzalez, Nelson; Rawson, Jeffrey; Izumi, Kenji; Koba, Naoya; Tsuchiya, Takanori; Kato, Hiroyuki; Omori, Keiko; Kandeel, Fouad; Mullen, Yoko; et al.
Abstract: The need for maintaining cell-spheroid viability and function within high-density cultures is unmet for various clinical and experimental applications, including cell therapies. One immediate application is for transplantation of pancreatic islets, a clinically recognized treatment option to cure type 1 diabetes; islets are isolated from a donor for subsequent culture prior to transplantation. However, high seeding conditions cause unsolicited fusion of multiple spheroids, thereby limiting oxygen diffusion to induce hypoxic cell death. Here we introduce a culture dish incorporating a micropyramid-patterned surface to prevent the unsolicited fusion and oxygen-permeable bottom for optimal oxygen environment. A 400 µ m-thick, oxygen-permeable polydimethylsiloxane sheet topped with micropyramid pattern of 400 µ m-base and 200 µ m-height was fabricated to apply to the 24-well plate format. The micropyramid pattern separated the individual pancreatic islets to prevent the fusion of multiple islets. This platform supported the high oxygen demand of islets at high seeding density at 260 islet equivalents cm −2, a 2–3-fold higher seeding density compared to the conventional islet culture used in a preparation for the clinical islet transplantations, demonstrating improved islet morphology, metabolism and function in a 4 d-culture. Transplantation of these islets into immunodeficient diabetic mice exhibited significantly improved engraftment to achieve euglycemia compared to islets cultured in the conventional culture wells. Collectively, this simple design modification allows for high-density cultures of three-dimensional cell spheroids to improve the viability and function for an array of investigational and clinical replacement tissues.